Can Exercise Make Us Smarter, Happier, and Have More Neurons? A Hormetic Perspective - Roy Ardian (Ridwan Institute, 2023)
The level of intensity in a fitness regimen determines its impact: exercising can enhance intelligence, boost happiness, and increase the number of neurons. It is commonly accepted that exercise programs yield both positive and negative outcomes, depending on their intensity, among other factors, following a pattern like hormesis with a two-phase dose response. In simple terms, hormetic stress is the exact amount of stress to which our body is challenged, but we are not too tired. Therefore, your body is not weakened by lack of exposure to stress, but you are spared from the harmful side effects of toxic stress. Nevertheless, no proof has emerged thus far regarding a two-phase reaction of specific agents responsible for these exercise-induced effects. The discussions and concepts will revolve around adult hippocampal neurogenesis (AHN) as a plausible physiological basis for the hermetic reaction to exercise in relation to its impact on cognition and mood, including the potential molecular pathways that might facilitate these effects.